2015
DOI: 10.1158/0008-5472.can-14-2538
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy and Breaking Immune Tolerance: New Approaches to an Old Challenge

Abstract: Cancer immunotherapy has proven to be challenging as it depends on overcoming multiple mechanisms that mediate immune tolerance to self-antigens. A growing understanding of immune tolerance has been the foundation for new approaches to cancer immunotherapy. Adoptive transfer of immune effectors such as antitumor monoclonal antibodies and Chimeric Antigen Receptor T cells bypasses many of the mechanisms involved in immune tolerance by allowing for expansion of tumor specific effectors ex vivo. Vaccination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
228
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(236 citation statements)
references
References 38 publications
0
228
0
8
Order By: Relevance
“…1 Stimulation of pattern-recognition receptors (PRR) induces maturation and activation of dendritic cells (DC), leading to secretion of pro-inflammatory cytokines such as IL-12 and type-I interferons, which are important for the effector functions of T and NK cells. 2,3 In this respect, nucleotide-sensing PRR such as toll-like receptor (TLR)3, TLR7, and RIG-I-like receptors (RLR) are of special interest for cancer therapy due to their potent stimulation of these cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…1 Stimulation of pattern-recognition receptors (PRR) induces maturation and activation of dendritic cells (DC), leading to secretion of pro-inflammatory cytokines such as IL-12 and type-I interferons, which are important for the effector functions of T and NK cells. 2,3 In this respect, nucleotide-sensing PRR such as toll-like receptor (TLR)3, TLR7, and RIG-I-like receptors (RLR) are of special interest for cancer therapy due to their potent stimulation of these cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…13 Accumulating data suggest that a critical determinant of therapeutic success is to overcome tumor-dependent immunosuppression. [14][15][16][17] Tumor-infiltrating T cells not only encounter a hostile microenvironment characterized by low oxygen and glucose conditions 18,19 but also active suppression by cells like regulatory T cells, tumor-associated macrophages or myeloid-derived suppressor cells (MDSC). 20,21 MDSC are a heterogeneous population of immature myeloid cells inhibiting antitumor reactivity of T and NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, tumors are rarely rejected spontaneously, reflecting their ability to maintain an immunosuppressive microenvironment [45]- [47] which is now known as immune tolerance. Multiple mechanisms used by tumor cells, including alteration of the antigen presentation machinery or secretion of immunosuppressive factors that can induce apoptosis of lymphocytes or activate negative regulatory pathways, can induce immune tolerance and limit the effectiveness of the immune response [48]. Documented studies have demonstrated many cancer-induced cells, cytokines and molecules contribute to the development of immune tolerance, including regulatory T cells, myeloid-derived suppressor cells, tumorassociated macrophages and other suppressor lymphocyte subsets such as interleukin-10 producing B cells, B regulatory cells, cytokines such as interleukin-10, transforming growth factor-beta and colony stimulating factor 1 [45] [48]- [50].…”
Section: Anticancer Drugs Developed From Anti-tumor Immunitymentioning
confidence: 99%
“…Many antibodies, cytokines, vaccines, and adoptive cell therapies are under development and some have been in the market, for example, ipilimumab and nivolumab are the latest and most potent monoclonal antibodies of cytotoxic T-lymphocyte antigen 4 and programmed death 1 expressed on T cells, respectively. Blocking those two inhibitory receptors keeps T cells active [48] [54]- [60]. Another example is the recent approval of the use of dinutuximab combination therapy for the treatment of high-risk neuroblastoma in paediatric patients.…”
Section: Anticancer Drugs Developed From Anti-tumor Immunitymentioning
confidence: 99%